Value determinants of indigenous craftsmanship - Rozaimie, Awang; Metom, Lilly (2024)
Indigenous craftsmanship is mostly referred to as the physical representation of intangible cultural heritage. UNESCO's 2003 Convention for the Safeguarding of Intangible Cultural Heritage defined intangible cultural heritage as "the practices, representations, expressions, knowledge, and skills—as well as the instruments, objects, artifacts, and cultural spaces associated therewith—that communities, groups, and, in some cases, individuals recognise as part of their cultural heritage” (UNESCO, 2023). However, the resolution of the convention gives prime credit to the abilities and knowledge required in the craft. Despite focusing on the actual craft pieces, preservation efforts should encourage craftsmen to continuously produce craft and descending their knowledge and skills, particularly to their heirloom and own communities. Conservation of the indigenous heirloom or buried ancestors’ treasure is limited to the tangible heritage that led the exploration estimation to the object values. Predominately, the indigenous knowledge underlying the creation of the craft object and the skills involved in the making of the craft object are varied. Thus, this writing is mainly initiated to provide insight into the determinants of valuing traditional craftsmanship.